On the Bounded Region for the Stratified Shear Flows in \(β\)-plane - Lavanya, S.; Ganesh, V.; Reddy, G. Venkata Ramana (Communications in Mathematics and Applications, 2023)
We consider incompressible, inviscid stratified shear flows in \(β\)-plane. We obtained a bounded and unbounded instability regions which depends on various parameters, and obtained a criterion for stability. Also, we obtained an upper bound for the growth rate, amplification factor of an unstable mode.